2002
DOI: 10.1002/1521-3951(200201)229:1<57::aid-pssb57>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical and Thermal Properties of Bulk Zn1?xBexTe Crystals

Abstract: Bulk Zn 1-x Be x Te crystals were grown in the range extending up to x ¼ 0.12. Their structural, optical and photothermal properties were characterised using X-ray diffraction, photoluminescence (PL) and photoacoustic (PA) methods. The lattice constants are found to follow a linear dependence on x. Energy gap and thermal diffusivity were determined from photoacoustic spectra. The energy-gap increasing trend with rising beryllium content is in agreement with that reported for thin (Zn,Be)Te layers on InP substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
2
5
0
Order By: Relevance
“…According to literature data [16][17][18][19][20], the possible donors are Al substituting for Zn (Al Zn ) or tellurium vacancies (V Te ), and the acceptors are V Zn or Ag Zn . The emission band in the energy range from 2.0 to 2.3 eV was observed for intentionally undoped ZnTe bulk crystals [12,21], as well as those doped with Al and Cl by thermal diffusion [17] and implanted with Al + , Zn + and Ar + [16,20]. The three main PL bands (2,371 eV, 2.325 eV and 2.2 eV in ZnTe) were observed for all Zn 1−x Be x Te crystals investigated.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…According to literature data [16][17][18][19][20], the possible donors are Al substituting for Zn (Al Zn ) or tellurium vacancies (V Te ), and the acceptors are V Zn or Ag Zn . The emission band in the energy range from 2.0 to 2.3 eV was observed for intentionally undoped ZnTe bulk crystals [12,21], as well as those doped with Al and Cl by thermal diffusion [17] and implanted with Al + , Zn + and Ar + [16,20]. The three main PL bands (2,371 eV, 2.325 eV and 2.2 eV in ZnTe) were observed for all Zn 1−x Be x Te crystals investigated.…”
Section: Resultsmentioning
confidence: 86%
“…The crystal bar obtained was cut into plates of about 1 mm thickness and mechanically polished. The structure and composition of the sample were determined by x-ray methods [12]. X-ray investigations showed that the compound crystallizes in the sphalerite structure type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are derived by fitting the bandgaps at a number of symmetry points in the binary compounds. The lattice constants were taken from the X-ray measurements (Paszkowicz et al 2002) and 350 plane waves were used for the calculations.…”
Section: Empirical Pseudopotential Methodsmentioning
confidence: 98%
“…Apart from the shift of the energy gap of the crystals from 2.28 eV for pure ZnTe crystals, to an average value of 2.35 eV for mixed crystals with a beryllium content x = 0.07, the spectra showed a considerable change of the shape with the frequency of modulation. This fact indicated the possibility of the existence of the complex crystal structure of the samples [16][17][18][19]. These experimental PPT spectra were then the focus of modeling with the inhomogeneous sample model.…”
Section: Inhomogeneous Sample Modelmentioning
confidence: 99%